Violence against woman: psychic and mental illness - Oliveira, Eliany Nazaré; Jorge, Maria Salete Bessa (Rev Rene, 2007)
The reflection tries to make explicit the existing interfaces between violence and mental illness, more specifically, inwomen experiencing daily mistreatment. Violence weakens women’s mental health. Psychological consequences of abuse are even more serious than their physical effects. Abuse suffering often destroys woman’s self esteem and exposes her to much higher risk of suffering mental disorders, including depression, post-traumatic stress, tendency towards suicide and consumption of drugs, such as tranquilizers and alcohol. Within this context, thousands of women are silently getting sick, without finding anyeone to identify, approach and to be the refuge for their problems.